Spray dried prodigiosin from Serratta Marcescens as a food colorant - Namazkar, Shahla (2013)
Pigments from microorganisms can serve as an alternative source to replace synthetic pigments used in the food industry. Natural pigments have some limitations including solubility, sensitivity and short stability upon exposure to light, pH and high temperature. Thus, encapsulation via spray drying can be employed to enhance the pigment’s properties. In this study, spray-dried microcapsules containing red pigment (prodigiosin) extracted from Serratia marcescens was produced using ?-carrageenan and maltodextrin as encapsulation agents. The effect of spray-drying parameters on the encapsulation yield (EY), particle size, moisture content and colour intensity of the prodigiosin microcapsules at different ratios of prodigiosin/encapsulation agent were studied. The most intense colour was obtained for the 1:1 ratio (volume ratio of prodigiosin in ethyl acetate to ?-carrageenan solution) using 200oC inlet temperature, feed flow rate of 60 m3/h, air pressure of 1.5 bar and feed rate of 3 mL/min. The encapsulated pigment is most stable in powder form at 0°C when stored in the dark, and thus has superior stability compared to pigment in its free form. Characterization of spray-dried prodigiosin using FTIR and FESEM confirmed that the particles were properly coated with encapsulating agents. The morphology showed the particles were regular shaped spheres with mean diameters between 0.5µm and 5µm. Finally, the particles were successfully applied to milk, yogurt and carbonated drinks. The results suggest that the spray-dried prodigiosin can be useful as a food colorant under the above optimum operating conditions.